The POSH scaffold protein is essential for signal coordination leading to CD8 T cell differentiation and survival - Guldenpfennig, Caitlyn; Guan, Yue; Cseri, Bela; Lopez, Elida; Teixeiro, Emma; Daniels, Mark (Frontiers in Immunology, 2025)
IntroductionUpon antigen recognition, naive CD8 T cells must induce c-JUN N-terminal kinase (JNK), NF-κB, and Akt signaling to drive differentiation and generate a heterogeneous effector response. While the roles of these three pathways individually in mediating essential cellular responses for CD8 T cell differentiation are well established, the mechanisms of signal integration and crosstalk between these pathways to produce a diverse and heterogeneous response to infection remain poorly understood. Here, we establish the critical role of the Plenty of SH3 Domains (POSH) scaffold protein in coordinating signals from all three pathways to support CD8 T cell differentiation and fate.MethodsUsing novel conditional T cell POSH knockout reporter mouse models (as POSHfl/fl CD4-Cre eGFP, POSHfl/fl GzmB-Cre eGFP), we determined the phenotype of T cells in the thymus and periphery through flow cytometry. Polyclonal and OT1 TCR transgenic POSH cKO CD8 T cells were stimulated in vitro and analyzed by flow cytometry to assess cell fate. JNK, NF-κB, and Akt pathways were examined via flow cytometry and immunoblotting. Purified OT1 CD8 T cells from these mice were adoptively transferred and subsequently challenged with VSV-OVA infection; their phenotype, effector function, and signaling were then assessed ex vivo by flow cytometry.ResultsWe demonstrate that POSH is essential for proper induction of the JNK, NF-κB, and Akt pathways. Furthermore, the absence of these signals due to POSH deficiency results in reduced differentiation into short-lived effector cells (SLECs), delayed proliferation, and decreased survival of memory precursor cells (MPECs) during the contraction phase.ConclusionsCollectively, these data identify POSH as a key regulator of CD8 T cell fate and enhance our understanding of the complex mechanisms governing signal integration during CD8 T cell responses to infection.